Transport Characteristics of Plasma Membranes of PK-15 Passaged Cells - Kuleshova, Larisa; Kovalenko, Igor; Kovalenko, Svetlana; Tsibulko, Tetiana; Gordienko, Olga (Problems of Cryobiology and Cryomedicine, 2021)
The values of permeability coefficients to water molecules and cryoprotectants are demanded to select the optimal duration of exposure of cells in cryoprotective media at the stage of their preparation for cryopreservation, as well as to find optimal cooling and warming rates during the freeze-thawing of cell suspensions. The necessary numerical values of such cell parameters as the osmotically inactive volume α and the surface-area-to-volume ratio γ were obtained for the analytical evaluation of the permeability coefficients of the PK-15 cells’ plasma membranes using physico-mathematical modelling. The permeability coefficients kp of the plasma membranes of PK-15 cells to 1,2-PD, EG, DMSO and glycerol cryoprotectants molecules, as well as the filtration coefficients Lp to water molecules at temperatures of 25, 15 and 5°C were determined by approximating the experimental data of the change in relative volume of cells on exposure time in the studied solutions by theoretical curves calculated on the basis of physical and mathematical model of passive transport of water and permeable substances under the condition of their maximum coincidence. The value of the activation energy of the transmembrane transfer of molecules of these substances is calculated Probl Cryobiol Cryomed 2021; 31(1): 014–022